Acquisitions, Entry and Innovation in Network Industries - Pehr-Johan Norbäck; Lars Persson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2011)
Why do so many high-priced acquisitions of entrepreneurial firms take place in network industries? We develop a theory of commercialization (entry or sale) in network industries showing that high equilibrium acquisition prices are driven by the incumbents' desire to prevent rivals from acquiring innovative entrepreneurial firms. This preemptive motive becomes more important when there is an increase in network effects. A consequence is higher innovation incentives under an acquisition relative to entry. A policy enforcing strict compatibility leads to more entry, but can be counterproductive by reducing bidding competition, thereby also reducing acquisition prices and innovation incentives.
Keywords: L10; L15; L26; L50; L86; O31; 330; Acquisitions; Commercialization; Compatibility; Entry; Network effects; Innovation; R&D; Regulation; Übernahme; Kommerzialisierung; Netzwerkökonomik; Innovation; Regulierung; E-Business; Theorie